PERBANDINGAN KEJADIAN KEHAMILAN PREEKLAMPSIA BERDASARKAN KOMPONEN METABOLIK - Yulia Margaretta Sari; Joserizal Serudji; Rizanda Machmud (Universitas Andalas, 2019)
In preeclampsia occurring carbohydrate and fat metabolism disorders. Components of the metabolic syndrome such as insulin resistance, obesity, and dyslipidemia contributes to the occurrence of preeclampsia. This was an obser-vational analytic study with Kohort design and has been performed in Obgyn Department of M. Djamil Hospital Padang, primary health care in Koto Berapak, Private Practice Midwive in Lintau from July 2013 to May 2014. 60 samples of second trimester of pregnancy with positive Roll over test. Each subject was examined BMI, fasting blood glucose, LDL, HDL, triglycerides, and insulin levels. Then divided into two groups, positive metabolic components group and negative metabolic components group. Statistical analysis to assess significance using the unpaired t test and chi square on SPSS 18.0 for windows. There was no significant association between metabolic components and preeclampsia (p> 0.05). Other metabolic components such as HDL level and insulin resistance were not statistically significant with preeclampsia (p> 0.05). HOMA IR examination also showed no significant association with the in-cidence of preeclampsia. However, the subgroup analysis showed a mean insulin levels higher in preeclampsia patients compared with normal pregnancies (p <0.05). BMI showed a significant association with preeclampsia (p <0.05). subgroup analysis showed a mean insulin levels higher in preeclampsia patients compared with normal pregnancies (p <0.05). BMI showed a significant association with preeclampsia (p <0.05). subgroup analysis showed a mean insulin levels higher in preeclampsia patients compared with normal pregnancies (p <0.05). BMI showed a significant association with preeclampsia (p <0.05).Keywords: Preeclampsia, metabolic syndrome, fasting blood glucose, LDL, HDL, triglycerides, HOMA-IR, BMI